Development of Futsal Learning Media Based on Augmented Reality 3D Visualization to Improve Physical Education Students Practicum Learning Results - Bogy Restu Ilahi; Syafrial; Fina Hiasa (UNIB Press, 2023)
This study aims to develop interactive learning media based on Android using the 3D Augmented Reality Visualization application as an innovation of practical and theoretical collaboration in one place in practicum learning, where learning in the 21st century is cross-learning for physical education students in futsal courses in the independent learning era. - independent campus. This study uses the Research and Development (R&D) method which refers to the 4D (four-D) research and development model, namely define, design, develop, and disseminate. The developed Android-based learning media will be tested on students taking the Futsal course, the FKIP UNIB Physical Education Study Program. The research instrument used to collect data in this study used questionnaires and test techniques. There are three questionnaires that will be distributed in this study, namely the material expert questionnaire, the media expert validation questionnaire, and the student response questionnaire. As a result, the total score obtained from the combined validation of material experts, media, and users is 139.5 or obtains an average value of 4.1, which means that the Android Based Futsal Learning Media with 3D Augmented Reality Visualization that the researchers developed falls into the category Suitable for use in learning activities.